Musicando a história e historiando a música em escolas de Caxias do Sul : 2008-2014 - Cettolin, Franciele (My University, 2016)
The corpus of this work deals with the teaching of music in schools coupled with the teaching of history, since both, as components of the national education system, have been recurrent themes in both academic debates and in the context of basic education. The Law of Directives and Bases of National Education, 1996 recommends working with cross-cutting issues, and suggests several methods that aim to cover the educational problems and bolster this multiculturalism in the school and community environment. In this sense, the research proposes to question the failure of Law No. 11,769 / 2008, which deals with the obligation of music in basic education, constituting as provocative discussions and considerations about music education, history and interdisciplinary issues between them. Based on the results of interviews applied along the history of public school teachers, municipal and state, of Caxias do Sul, intends to evaluate the existing teaching and learning materials on the subject and the consequent practices of teachers in the classroom. From this, he craved to build an affordable material and teacher support you want to work with music in history classes, beyond what is already proposed in order to consider the sublime. The methodology used was based on the literature review with emphasis on cultural history proposed by Roger Chartier, along with interviews that comprised an analysis, especially, qualitative data, plus all bibliographic field visited about the teaching of the subjects in question. Finally, it was concluded that Music provides support for elementary education since the proximity of the same with your day to day allows relationships that go beyond the purely theoretical questions, enabling by reading various musical signs interpretations in more various fields of knowledge, especially in the humanities and in particular, the teaching of History, meaning the awareness of self and other.
O corpus deste trabalho trata do ensino da Música na escola aliado ao ensino da História, uma vez que ambos, como componentes do sistema nacional de ensino, têm sido temas recorrentes nos debates tanto acadêmicos como no âmbito da educação básica. A Lei de Diretrizes e Bases da Educação Nacional, 1996, recomenda o trabalhado com temas transversais e sugere metodologias diversas que almejam abranger os problemas educacionais e amparar o multiculturalismo presente no meio escolar e comunitário. Neste sentido, a pesquisa propõe problematizar o não cumprimento da Lei nº 11.769/2008 que trata sobre a obrigatoriedade da música na educação básica, se constituindo como provocadora de debates e ponderações acerca do ensino de Música, História e questões interdisciplinares entre ambas. Tendo por base o resultado de entrevistas aplicadas junto a professores de história de escolas públicas, municipais e estaduais, de Caxias do Sul, pretende ainda avaliar o material didático e pedagógico existente sobre o assunto e as consequentes práticas dos professores em sala de aula. A partir disto, almejou-se construir um material acessível e de apoio ao professor que pretende trabalhar com a Música nas aulas de História, além do que já é proposto, de forma a considerar o sublime. A metodologia utilizada baseou-se na revisão bibliográfica com ênfase na história cultural proposta por Roger Chartier, juntamente com as entrevistas que compuseram uma análise, sobretudo, qualitativa dos dados, além de todo campo bibliográfico visitado a respeito do ensino das disciplinas em questão. Por fim, concluiu-se que a Música oferece amparo para a formação do educando uma vez que a proximidade da mesma com o seu dia a dia permite relações que ultrapassam as questões puramente teóricas, possibilitando através da leitura de vários signos musicais, interpretações nos mais diversos campos do saber, principalmente na área de ciências humanas e em particular, no ensino de História, significando a consciência de si e do outro.
Keywords: História - Estudo e ensino; Ensino - Metodologia - Música; Abordagem interdisciplinar do conhecimento na educação; Escolas - Caxias do Sul (RS); History - Study and teaching; Teaching - Methodology - Music; Interdisciplinary approach in education; Schools - Caxias do Sul (Brazil)